2018
DOI: 10.2174/1874836801812010269
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of CFRP Orientation Angle on the Shear Strength of RC Beams

Abstract: Background:Carbon Fiber Reinforced Polymer (CFRP) sheets are widely used for strengthening and repairing reinforced concrete structures. Previous experimental studies have shown that strengthening Reinforced Concrete (RC) beams with CFRP sheet can be greatly influenced by the configuration, orientation and properties of the CFRP sheets.Objective:The behaviour of RC beams, strengthened with 60° and 45° inclined CFRP sheets, has not clearly explained.Method:Thus, an experimental program, proposed in this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Additionally, the TR55 design model displayed a significant underestimation of the total shear force capacity for the tested beams. Murad [ 124 ] evaluated different orientations of FRP used for the fortification of beams through EBR. Through experimentation, it was found that the 63° inclined CFRP had a remarkable impact on increasing the shear strength and ultimate deflection of the specimen.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Additionally, the TR55 design model displayed a significant underestimation of the total shear force capacity for the tested beams. Murad [ 124 ] evaluated different orientations of FRP used for the fortification of beams through EBR. Through experimentation, it was found that the 63° inclined CFRP had a remarkable impact on increasing the shear strength and ultimate deflection of the specimen.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Also, it has a unique property to deal with different sectional shapes and corners for strengthening applications and shear retrofitting. Numerous structures need to be strengthened due to the fundamental increase in the applied loads, cruel environment, and poor maintenance [3]. Using CFRP to strengthening the shear in beams has been attracted tremendous attention lately.…”
Section: Introductionmentioning
confidence: 99%
“…They have found that the bond capacity is controlled by the diameter, length, and the angle of inclination of the anchors. Murad (2018aMurad ( , 2018b has found that CFRP sheets' orientation angle has significant effect on the peak load and deflection of reinforced concrete members. Ozbakkaloglu, Fang, and Gholampour (2017) have studied the effect of fiber-reinforced polymer (FRP) anchor configuration on the behavior of FRP plates externally bonded on concrete members.…”
Section: Introductionmentioning
confidence: 99%